Quaternionic Local Ranking Binary Pattern A Local Descriptor of Color Images - Lan, Rushi (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2016)
This paper proposes a local descriptor called quaternionic local ranking binary pattern (QLRBP) for color images. Different from traditional descriptors that are extracted from each color channel separately or from vector representations, QLRBP works on the quaternionic representation (QR) of the color image that encodes a color pixel using a quaternion. QLRBP is able to handle all color channels directly in the quaternionic domain and include their relations simultaneously. Applying a Clifford translation to QR of the color image, QLRBP uses a reference quaternion to rank QRs of two color pixels, and performs a local binary coding on the phase of the transformed result to generate local descriptors of the color image. Experiments demonstrate that the QLRBP outperforms several state-of-the-art methods